2015
DOI: 10.1371/journal.pcbi.1004165
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally Verified Parameter Sets for Modelling Heterogeneous Neocortical Pyramidal-Cell Populations

Abstract: Models of neocortical networks are increasingly including the diversity of excitatory and inhibitory neuronal classes. Significant variability in cellular properties are also seen within a nominal neuronal class and this heterogeneity can be expected to influence the population response and information processing in networks. Recent studies have examined the population and network effects of variability in a particular neuronal parameter with some plausibly chosen distribution. However, the empirical variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 47 publications
3
65
0
Order By: Relevance
“…Both components are determined from the Fokker-Planck system and can be conveniently calculated without having to solve Eqs. (17)- (19) forward in time: the linear temporal filter is obtained from the first order spike rate response to small amplitude modulations of the mean input and the nonlinearity is obtained from the steady-state solution [57,58]. The filter is approximated by an exponential function and adapted to the input in order to allow for large deviations of µ.…”
Section: Methods 2: Derived Spike Rate Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Both components are determined from the Fokker-Planck system and can be conveniently calculated without having to solve Eqs. (17)- (19) forward in time: the linear temporal filter is obtained from the first order spike rate response to small amplitude modulations of the mean input and the nonlinearity is obtained from the steady-state solution [57,58]. The filter is approximated by an exponential function and adapted to the input in order to allow for large deviations of µ.…”
Section: Methods 2: Derived Spike Rate Modelmentioning
confidence: 99%
“…Comparisons between models of this type and recorded spike trains have revealed that multiple combinations of biophysical parameters give rise to the same firing patterns [8,9]. This observation motivates the use of models at an intermediate level of complexity, and in particular integrate-and-fire (I&F) neurons, which implement in a simplified manner the key biophysical constraints with a reduced number of effective parameters and can be equipped with various mechanisms such as spike initiation [10][11][12], adaptive excitability [13,14] or distinct compartments [15,16] to generate diverse spiking behaviors [17,18] and model multiple neuron types [19,20]. I&F models can reproduce and predict neuronal activity with a remarkable degree of accuracy [11,21,22], essentially matching the performance of biophysically detailed models with many parameters [17,23]; thus, they have become state-of-the-art models for describing neural activity in in-vivo-like conditions [11,19,20,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative, prominent class of models with reduced complexity are spiking neuron models of the integrate-and-fire (I&F) type, which implement in a simplified manner essential biophysical constraints. These models have been advanced in recent years to accurately predict neuronal activity [20][21][22] and classify multiple neuron types [17,23,24]. They have become state-of-the-art models for describing neural activity in in-vivo-like conditions and have been applied in a multitude of studies on neural network dynamics.…”
Section: Introductionmentioning
confidence: 99%